Transition to open: A metrics analysis of discoverability and accessibility of LIS scholarship - Jaya Raju (South African Journal of Science, 2019)
Metrics analysis of journal content has become an important point for debate and discussion in research and in higher education. The South African Journal of Libraries and Information Science (SAJLIS), a premier journal in the library and information science (LIS) field in South Africa, in its 85-year history, has had multiple editors and many contributing authors and has published over 80 volumes and 160 issues on a diversity of topics reflective of LIS theory, policy and practice. However, how discoverable and accessible has the LIS scholarship carried by the Journal been to its intended readership? SAJLIS transitioned to open access in 2012 and this new format in scholarly communication impacted the Journal significantly. The purpose of this paper is to report on a multiple metrics analysis of discoverability and accessibility of LIS scholarship via SAJLIS from 2012 to 2017. The inquiry takes a quantitative approach within a post-positivist paradigm involving computer-generated numerical data as well as manual data mining for extraction of qualitative elements. In using such a multiple metrics analysis to ascertain the discoverability and accessibility of LIS scholarship via SAJLIS in the period 2012 to 2017, the study employs performance metrics theory to guide the analysis. We highlight performance strengths of SAJLIS in terms of discoverability and accessibility of the scholarship it conveys; identify possible growth areas for strategic planning for the next 5 years; and make recommendations for further study for a more complete picture of performance strengths and areas for improvement.